The MAFIOTISMUS – the newest kind of personal and private capitalism on state niveau – on the examples in Bulgaria and European Commission based on the Momtchil Dobrev’s "Theory of generate of crises", Momtchil Dobrev’s “Theory and praxis of Mafiotismus” and on the Momtchil Dobrev’s "Theory of the mafia" - Dobrev-Halachev, Momtchil; Garibova, Mariola; Dobreva, Mariika; Garibov, Alexander (Archives of Business Research, 2018)
Lord prof PhD PhD Momtchil Dobrev-Halachev developed 2008 “Theory of generating of crises “ , 2010 “Theory and praxice of the Mafiotismus” and 2001 “ Theory of the mafia”. Based on these two theories this paper explane the establishment of the mafiotismus all over the world – principles, theory and praxis in European Union , European Commission and in the Republic Bulgaria